Incorporation of Soybean Meal and Hazelnut Meal in Diets for Black Sea Turbot (Scophthalmus Maeoticus) - Ergün, S.; Yigit, M.; Türker, A.; Harmantepe, B. (My University, 2008)
The effects of soybean and hazelnut meals as partial replacements of fishmeal were studied in Black Sea turbot (Scophthalmus maeoticus). Juvenile fish (mean 26 g) were fed six isoenergetic (19.1±0.18 kJ /g diet) and isonitrogenous (511±0.48 g protein/kg diet) diets for 60 days. The control diet contained fishmeal as the sole protein source. In two of the six experimental diets, soybean meal replaced 20% and 35% of the fishmeal. The other three diets contained 65% fishmeal plus soybean and hazelnut meal at ratios of 25/10, 15/20, 5/30. There was no significant difference (p<0.05) in growth performance between the groups fed the diet containing 20% soybean meal and those fed the control diet. Fish fed the 10% or 20% hazelnut meal diets had similar results as fish fed the diet containing 35% soybean meal. Growth performance, feed utilization, protein efficiency, and nitrogen retention were significantly lower in the group fed the 30% hazelnut diet. Total nitrogen excretion and retention were similar in all groups except the 30% hazelnut group. Results indicate that soybean meal can replace up to 20% of the fishmeal without causing reduction in growth performance, nutrient utilization, or nitrogen retention and that hazelnut meal can be incorporated with 20%, but not 35%, soybean meal at a level of no more than 20% of the diet.
Keywords: Black Sea Turbot; Feed Utilization; Fishmeal; Hazelnut Meal; Soybean Meal